IMPROVING STUDENT’S READING COMPREHENSION THROUGH COLLABORATIVE STRATEGIC READING - Ni Made Ernila Junipisa; Ni Putu Lindawati (LITERA : Jurnal Bahasa Dan Sastra, 2018)
ABSTRACTThis research is aimed to find out whether or not the implementation of Collaborative StrategicReading (CSR) improves students' reading comprehension. CSR is reading strategy that employsfour strategies namely Preview, Click and Clunk, Get the Gist and Wrap Up during students’learning activities. A class of accounting class in STIE Triatma Mulya is participated as theparticipant of the study. The required data were collected through the use of questionnaire,observation checklist, and reading test. The data from the questionnaire indicated that students hadpositive attitude toward the implementation of CSR. They feel that CSR improves their motivationin learning English and CSR brings more fun to the process of learning. Moreover, it was foundfrom observation data that the students were actively participated during CSR implementation andthey were motivated when comprehending a text by means CSR strategy. Finally, the study provedthat CSR improved students’ reading comprehension. Students’ mean score of reading test in thebeginning of the study was 50.6 meanwhile, after applying CSR as reading strategy, their meanscores improved to 67,80.2 and 88.7Keywords: Collaborative Strategic Reading, Reading Comprehension, Action Research.ABSTRAKPenelitian ini bertujuan untuk mengetahui apakah penerapan Collaborative Strategic Reading(CSR) meningkatkan pemahaman membaca siswa. CSR adalah sebuah strategi yangmenggunakan empat langkah yaitu Preview, Click dan Clunk, Get the Gist dan Wrap Up selamakegiatan pembelajaran . Sebuah kelas akuntansi di STIE Triatma Mulya berpartisipasi sebagaipeserta penelitian. Data yang diperlukan dikumpulkan melalui penggunaan kuesioner,observasi,dan tes membaca. Data dari kuesioner menunjukkan bahwa siswa memiliki sikap positif terhadappelaksanaan CSR. Mereka merasa bahwa CSR meningkatkan motivasi mereka dalam belajar danmembawa lebih banyak kesenangan pada proses belajar. Selain itu, ditemukan dari data observasibahwa siswa secara aktif berpartisipasi selama pelaksanaan CSR dan mereka termotivasi ketikamemahami teks dengan cara strategi CSR. Akhirnya, penelitian membuktikan CSR yangmeningkatkan pemahaman membaca siswa. Nilai rata-rata siswa yang membaca sebesar 50.6 diawal penelitian sementara itu, setelah menerapkan CSR sebagai strategi membaca, skor rata-ratamereka ditingkatkan menjadi 67,80.2 dan 88.7Kata kunci: Collaborative Strategic Reading, Pemahaman Membaca, Penelitian Tindakan Kelas.